To the Question of the Constitution of the Russian Federation Influence on the Regulation of Local Government - Oleg J. Gorkovchenko (Èkonomika, Pedagogika i Pravo, 2014)
In the present article author considers questions of influence of the Constitution of the Russian Federation on regulation of questions of local government. Author also analyzes practice of work of the Constitutional Court of the Russian Federation, and also a role of a legal position of the Constitutional Court of the Russian Federation. In the conclusion author emphasizes that the population of municipality has to be provided with all necessary organizational and legal resources for the solution of questions of local value.